Testing a gender transformative approach combined with a fish harvesting technology for women - Choudhury, Afrina (WorldFish, 2017)
Presented by Afrina Choudhury (World Fish), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.